Rainwater harvesting and Leucaena leucocephala biomass rates effects on soil moisture, water use efficiency and Sorghum bicolor [(L.) Moench] productivity in a semi‐arid area in Zimbabwe. (1st June 2022) - Kugedera, Andrew T; Mandumbu, Ronald; Nyamadzawo, George
Abstract: BACKGROUND: Sorghum is one of the major staple crops in Sub Saharan Africa but its production is mainly limited by moisture stress, frequent droughts and soil infertility, especially in the smallholder farming systems. This raises the need to develop climate smart options to improve sorghum production. The objective was to assess the effects of rainwater harvesting and use of different Leucaena leucocephala biomass rates on soil moisture content, rainwater use efficiency, and stover and grain yields in two sorghum varieties (Macia and SV1). The experiment was laid as a randomized complete block design in split‐split plot arrangement from 2017/2018 to 2019/2020 season. RESULTS: The results show that tied contour (TC) and infiltration pits (IPs) significantly ( P  < 0.05) increased soil moisture content than standard contour (SC). Soil moisture content increased gradually with the increase in soil depth (20–40 cm > 0–20 cm), with 2018/2019 season having the maximum soil moisture content. Soil moisture content also increased with the increase in application rates of Leucaena biomass. Grain and stover yields were significantly ( P  < 0.05) increased by all Leucaena biomass application rates with higher yield observed in 2018/2019 season. SC had significantly lower grain and stover yields at all Leucaena biomass application rates. TC and IPs had comparable rainwater use efficiency compared to SC. Rainwater use efficiency increased with application rates of Leucaena biomass across all seasons and varieties. CONCLUSION: TC and IPs are better adaptive mechanisms against drought spells in semi‐arid areas and can be combined with 10 t ha −1 of Leucaena biomass due to better yield increments realized. © 2022 Society of Chemical Industry.